Chapter Storage and Food Control in the 'Amuq from the Late Bronze to the Iron Age: The Archaeological Evidence - PUCCI, MARINA (Studia Asiana, 2023)
Ongoing study of the pottery assemblage and its surrounding context in Area 4 at the site of Alalakh has again brought to light a phenomenon that is considered typical for the Iron Age I Levant: the construction of pits/silo installations in open areas. This phenomenon has been interpreted as a sign of ruralisation or insecure economic conditions, a possible marker for the political instability in the area during the 13th-12th centuries BCE. This article examines the similarities and differences between the examples from the Iron Age I in the 'Amuq and contemporary sites in the Levant, and also considers later similar installations from the Iron Age II. Keeping in mind the functions usually ascribed to these structures, this study also analyses the so-called 'Anatolian' tradition of grain storage in the Late Bronze Age and Early Iron Age in order to address the role of these installations in understanding possible food control strategies and their possible impact in the Levant.